2006
DOI: 10.1007/s10803-006-0147-5
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Emotional Problems in Young People with Pervasive Developmental Disorders: Relative Prevalence, Effects of Subject Characteristics, and Empirical Classification

Abstract: Parents or teachers rated 487 non-clinically referred young people with Pervasive Developmental Disorders on the Nisonger Child Behavior Rating Form. The objectives of the study were to examine the relative prevalence of specific behavior problems, assess the impact of subject characteristics, and derive an empirical classification of behavioral and emotional problems for this population. Results indicated that the youngsters experienced high rates of behavior and emotional problems. Cluster analysis suggested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
265
0
8

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 475 publications
(289 citation statements)
references
References 29 publications
16
265
0
8
Order By: Relevance
“…A meta-analysis of research on maladaptive behaviors in children and adults with different types of intellectual disabilities found that aggression, disruptive behavior, and selfinjury were significantly more prevalent among those with ASD than other types of intellectual disabilities (McClintock, Hall, & Oliver, 2003). However, a recent study of 487 school children with pervasive developmental disorders (Lecavalier, 2005) found the least prevalent maladaptive behaviors were selfinjury and physical aggression. Clearly, more research is needed to confirm the prevalence of different types of maladaptive behaviors among those with an autism spectrum disorder.…”
Section: Prevalence and Change In Maladaptive Behaviors In Adolescencmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis of research on maladaptive behaviors in children and adults with different types of intellectual disabilities found that aggression, disruptive behavior, and selfinjury were significantly more prevalent among those with ASD than other types of intellectual disabilities (McClintock, Hall, & Oliver, 2003). However, a recent study of 487 school children with pervasive developmental disorders (Lecavalier, 2005) found the least prevalent maladaptive behaviors were selfinjury and physical aggression. Clearly, more research is needed to confirm the prevalence of different types of maladaptive behaviors among those with an autism spectrum disorder.…”
Section: Prevalence and Change In Maladaptive Behaviors In Adolescencmentioning
confidence: 99%
“…Despite the explicit emphasis on development and lifelong impacts, there has been relatively little research examining how the symptoms of autism change across the life course (see Seltzer, Shattuck, Abbeduto, & Greenberg, 2004, for a review). Furthermore, although maladaptive behaviors are often comorbid with ASDs (American Psychiatric Association, 2000), little is known about the manifestation of maladaptive behaviors in this population (Lecavalier, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Several authors mentioned that learning problems are regularly occurring in individuals with developmental disabilities and mental retardation [15,30,31]. Adolescents with mental disorders and developmental disabilities are attributed a higher risk of emotional and behavioral problems [32][33][34] and substance abuse [35,36] compared with their healthy peers. Moreover, it was found that individuals with learning impairments, emotional and behavioral problems or substance abuse experience significant higher unemployment rates than the general population [37][38][39].…”
Section: Disabil Rehabil Downloaded From Informahealthcarecom By Unimentioning
confidence: 99%
“…5,7 A high percentage of children with ASD also exhibit disruptive behavior, including tantrums, aggression, self-injury, hyperactivity, impulsiveness, and noncompliance. 8,9 These cooccurring behavioral problems pose enormous challenges to parents, may result in restrictive school placement, and undermine interventions in the home and community. 10 Disruptive behavior may actually contribute to adaptive skill deficits.…”
Section: Introductionmentioning
confidence: 99%